2002
DOI: 10.1271/bbb.66.1337
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Acetate Metabolism inCorynebacterium glutamicumUsing a Newly Developed Metabolic Array

Abstract: Following the determination of the whole-genome sequence of Corynebacterium glutamicum, we have developed a DNA array to extensively investigate gene expression and regulation relevant to carbon metabolism. For this purpose, a total of 120 C. glutamicum genes, including those in central metabolism and amino acid biosyntheses, were amplified by PCR and printed onto glass slides. The resulting array, designated a "metabolic array", was used for hybridization with fluorescently labeled cDNA probes generated by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 1 publication
4
49
0
Order By: Relevance
“…In addition, recent genome-wide expression analyses of C. glutamicum cells grown on glucose and on acetate substantiated the idea of this transcriptional regulation of the aceA, aceB, pta, and ack genes (14,21,35). In accordance with induction or repression of these genes by a common regulator protein(s), in front of the genes we observed highly conserved 13-bp motifs (AA/GAACTTTGCAAA) showing a dyad symmetry at one end (underlined) (14).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…In addition, recent genome-wide expression analyses of C. glutamicum cells grown on glucose and on acetate substantiated the idea of this transcriptional regulation of the aceA, aceB, pta, and ack genes (14,21,35). In accordance with induction or repression of these genes by a common regulator protein(s), in front of the genes we observed highly conserved 13-bp motifs (AA/GAACTTTGCAAA) showing a dyad symmetry at one end (underlined) (14).…”
supporting
confidence: 73%
“…Recent genome-wide and comparative expression analyses with C. glutamicum grown on glucose and on acetate revealed that in addition to the pta-ack operon and the aceA and aceB genes, a variety of other genes are obviously under transcriptional control in response to the presence or absence of acetate in the growth medium (14,21,35). These genes (thus belonging to the acetate stimulon) include those for some of the enzymes of the tricarboxylic acid cycle (citrate synthase, aconitase, succinate dehydrogenase subunits A, B, and C/D, and fumarase) and for some of the enzymes involved in sugar metabolism (glucose-specific phosphotransferase system enzyme II, glucose-6-phosphate dehydrogenase, transaldolase, transketolase, pyruvate kinase, and pyruvate dehydrogenase complex E1 subunit).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional regulator GlxR contains a domain with similarity to the cAMP-binding motifs of Crp from E. coli and, in fact, cAMP is essential for binding of GlxR to the aceA/aceB intergenic region in C. glutamicum (Kim et al, 2004;Letek et al, 2006). The regulation of C. glutamicum metabolism in the presence of various carbon sources clearly differs from that of E. coli or B. subtilis (Gerstmeir et al, 2003;Hayashi et al, 2002;Letek et al, 2006;Muffler et al, 2002). No direct evidence has been found of a CCR system in C. glutamicum (Bruckner & Titgemeyer, 2002;Gerstmeir et al, 2003;Han et al, 2007), although a CCR-like phenomenon has been reported from cells grown on medium containing glucose with either glutamate (Gerstmeir et al, 2003;Kramer et al, 1990;Kronemeyer et al, 1995) or ethanol (Arndt & Eikmanns, 2007;Kotrbova-Kozak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon source-dependent regulation of gene expression in C. glutamicum has been investigated by comparing the expression profile in glucose-grown cells to that in acetate-grown cells (28)(29)(30). These studies reveal that genes for sugar uptake and metabolism, including the phosphotransferase system and glycolysis, are upregulated in the presence of glucose.…”
mentioning
confidence: 99%